COGNITIVE BEHAVIOR THERAPY AS AN EFFORT TO IMPROVE ELDERLY INDEPENCE IN THE COVID-19 PANDEMIC - Yanis Kartini; Siti Damawiyah; Bambang Edi Suwito; Imamatul Faizah (Community Service Journal of Indonesia, 2022)
The ongoing Covid 19 pandemic in Indonesia has an impact on psychosocial conditions for everyone. The elderly is a vulnerable group for COVID-19, the elderly experiences a decrease in the ability of body functions both physically and psychologically of a physiological nature. Decreased body function in the elderly is caused by changes in muscle morphology and degenerative diseases, these can cause health problems in the elderly. The implementation of this community service activity aims to teach Cadres and the elderly about Cognitive Behavior Therapy as an effort to increase the independence of the elderly during the COVID-19 pandemic. The method used in this community service activity is to provide training and education health services. This activity was carried out during April-May 2022 which was attended by 12 health cadres and 22 residents in RW 06 Wonokromo Village, Surabaya. The results show that the activity has achieved success according to the success indicators that have been set, namely as many as 12 health cadres were successfully recruited; average attendance is 100%, participants participate in activities enthusiastically, knowledge of cadres after training and residents after counseling increases significantly.